Effectiveness of a single intra-articular bone marrow aspirate concentrate (BMAC) injection in patients with grade 3 and 4 knee osteoarthritis - Themistocleous, George S. (Heliyon, 2018)
AIM: To evaluate the clinical efficacy and safety of an intra-articular injection of bone marrow aspirate concentrate (BMAC) as a treatment option for osteoarthritis (OA) of the knee. MATERIALS AND METHODS: Between June 2014 and February 2017, data from 233 patients with knee osteoarthritis treated with BMAC injection at a single center, were retrospectively evaluated. Only patients with idiopathic osteoarthritis were included. Exclusion criteria were post-traumatic osteoarthritis, previous knee surgery, age less than 50 years old or more than 85 years old, active infection, uncontrolled diabetes mellitus, rheumatological or other systemic disease, malignancy, or treatment with immunosuppressive drugs. Bone marrow from the iliac crest was aspirated/concentrated with a standardized technique using a single-spin manual method. Patients were evaluated before and after the procedure, using the numeric pain scale (NPS) and Oxford knee score (OKS). Mean follow-up period was 11 months, range (6–30 months). RESULTS: A total of 121 of 233 patients had completed data as previously defined and were included in the statistical analysis. There were 85 females and 36 males, with mean age 70 years (range 50–85). Compared to baseline, the mean NPS decreased from 8.33 to 4.49 (p < 0.001) and the mean OKS increased from 20.20 to 32.29 (P < 0.001) at final follow-up. There were no complications. CONCLUSION: A single intra-articular injection of BMAC is a safe and reliable procedure that results in clinical improvement of knee OA.